Analysis of Kemijeu Kelor (Moringa Oleifera) Herbal Teabag, Mint (Pappermint) and Bungong Jeumpa (Michelia Champaca) - Ceudah Munirah; Nurmahni Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Kemijeu herbal tea is made from Moringa leaves, mint leaves, and Bungong Jeumpa. Kemijeu herbal tea is rich in benefits, one of which is to increase body immunity and reduce cholesterol, so Kemijeu tea can be said to be an innovation from herbal tea in general. The purpose is to determine the analysis of Kemijeu herbal teabags of Moringa (Moringa oleifera), Mint (Peppermint), and Bungong Jeumpa (Michelia champaca). I made Kemijeu herbal tea using an experimental approach. According to Sugiyono (2018), the experimental method is a research method used to study the effect of one thing on another in controlled conditions systematically, logically, thoroughly, and by controlling the realism of the results obtained. The conclusion of this Kemijeu herbal tea research is that this tea is much loved because it has a delicious aroma and taste and unique color and texture. This tea also meets the requirements of the SNI 3836:2013 dry tea category because it matches the character of tea in general.